Capturing waste heat energy with charge-transfer organic thermoelectrics - Dimitrov, Vladimir; Woodward, Simon (Thieme, 2018)
Electrically conducting organic salts, known for over 60 years, have recently demonstrated new abilities to convert waste heat directly into electrical power via the thermoelectric effect. Multiple opportunities are emerging for new structure-property relationships and new materials to be attained through synthetic organic chemistry. This review highlights key aspects of this field, which is complimentary to current efforts based on polymeric, nanostructured or inorganic thermoelectric materials and indicates opportunities whereby main stream organic chemists can contribute.